The Impact of Cryptocurrency on Traditional Bank Industry: A Literature Review - Ko, Jiun Hau; Mohd Waliuddin, Mohd Razali; Shazali, Shaharuddin (OPRA publications, 2024)
Nowadays, there has been a noticeable upsurge in the use of cryptocurrencies, which has coincided with important developments in artificial intelligence technology that have advanced blockchain procedures to new heights of maturity. This convergence has strengthened cryptocurrencies' dependability in addition to making them more feasible. But this development seriously jeopardizes the standing of Malaysian financial institutions, especially in the banking sector. With their ever-expanding range of benefits, cryptocurrencies immediately threaten the established roles of banks and even provide further advantages. By analyzing the reactions of the financial industry to the emergence of cryptocurrencies can to uncover potential strategies for banks to mitigate the challenges posed by this disruptive technology. Through an examination of relationship among the bank deposit, capital adequacy ratio, and the market capitalization of cryptocurrency, it helps to explore how the adoption of cryptocurrencies may reshape the banking sector and influence macroeconomic dynamics.